High Risk Behaviour Tertular HIV/AIDS pada Anak Buah Kapal - Mansur Sididi; Rahman Rahman; Yusriani Yusriani (Jurnal Kesmas Asclepius, 2020)
The purpose of this study was to analyze the factors that influence the high risk behavior of contracting HIV / AIDS on ship crews in Makassar City. This type of research is a quantitative study with a cross sectional study design. The results showed that there was no influence of knowledge and support from health workers with the high risk behavior of contracting HIV / AIDS on ship crew at Soekarno-Hatta Port because crew members already know a lot about transmission from HIV / AIDS and are also supported by the education level of ABK (p. value> 0.05). In conclusion, knowledge and the role of health workers had no effect on the high risk behavior of contracting HIV / AIDS among ship crew. Keywords: Crew, Behavior, High Risk